Coeliac disease as a systemic disorder - current state of knowledge - Strzałkowska, Paulina; Hobot, Maciej; Grabski, Wojciech; Szaj, Dominika; Raczkowska, Michalina; Mazur, Aleksandra (Quality in Sport, 2025)
Coeliac disease is a chronic autoimmune disorder triggered by gluten ingestion in genetically predisposed individuals, primarily those carrying the HLA-DQ2 and HLA-DQ8 alleles. Although it was previously considered a condition limited to the gastrointestinal tract, it is now recognized as a systemic disease. In addition to classical intestinal symptoms (diarrhea, abdominal pain, malabsorption), coeliac disease can cause extraintestinal manifestations affecting the musculoskeletal, neurological, endocrine, dermatological, and hepatic systems. If left untreated, it is associated with an increased risk of malignancies, including enteropathy-associated T-cell lymphoma (EATL) and adenocarcinoma of the small intestine. The cornerstone of treatment remains a strict gluten-free diet, which alleviates symptoms and reduces the risk of complications. The aim of this review is to present the current state of knowledge regarding the systemic manifestations of coeliac disease, the underlying pathogenic mechanisms, and the impact of treatment on disease course and quality of life. Emphasis is placed on the importance of early diagnosis and individualized patient management.